Diagnosing trichinellosis in pigs slaughtered at a major abattoir in Lagos State Nigeria (2014)
Trichinellosis, an infection caused by the Trichinella spp has been known to occur worldwide affecting almost all species of animals including man. It is an emerging or re- emerging disease in developed and developing countries. This survey was conducted to investigate the prevalence of trichinellosis in domestic pigs slaughtered in Lagos, Nigeria. Nine hundred pig sera were collected at slaughter in an abattoir in Lagos state. The sera samples were stored frozen at the parasitology research laboratory of the department of Veterinary Microbiology and Parasitology, University of Ibadan till used. Post mortem examination was also carried out for 350 carcasses of the 900 from which blood samples were collected using standard procedures. 53 out of the 900 samples collected were seropositive for Trichinella E/S antigen using ELISA kit. No Trichinella cysts were found at postmortem examination. One of the sample positive at serology was negative at postmortem. A total sero- prevalence of 5.89% was obtained, 5.83 % (adults) and 7.65% of growers were positive. There was no serological evidence of trichinellosis in samples (44) collected from weaners. The male pigs had a higher prevalence (6.14%) than the females (5.45%). However, the differences between the ages and the sexes were not statistically significant (P≤ 0.05).This study has been able to provide serological evidence of the presence of trichinellosis in this state and thus the need to carry out proper postmortem examination after slaughter. Also, the absence of cyst at postmortem and the presence of antibodies at serology show that postmortem examination is not enough to screen for Trichinella in slaughtered food animals hence the need for the establishment of diagnostic laboratories at abattoirs in the country